The Friendship Circle Phenomenon: A Case Study at MTs Surya Buana Malang - Pitriyah, Umi; Sari, Indah Yulitalia; Hotifah, Yuliati; Safitri, Jihan; Pratiwi, Awalya Siska (Proceedings Series of Educational Studies, 2024)
Friendships play a crucial role in shaping the well-being and development of adolescents. Nowadays, friendships often form within groups known as friendship circles. However, these friendship circles can have both positive and negative effects. At MTs Surya Buana, several issues have arisen due to these circles, such as self-isolation, lack of self-confidence, feelings of alienation, and withdrawal from social interaction. This study aims to investigate additional aspects of friendship circles, such as social skills, concern, and empathy experienced by individuals both inside and outside the circles. The research method used is qualitative with a case study approach, involving students and educators from MTs Surya Buana. Data were collected through unstructured interviews with three informants selected based on the criteria of the research subjects. The results show that students within friendship circles still exhibit low levels of social skills, concern, and empathy, indicating the need for more effective and efficient efforts to improve these areas.